2021
DOI: 10.1017/aer.2021.54
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new design with generic modeling and adaptive control of a transformable quadrotor

Abstract: Recently, transformable Unmanned Aerial Vehicles (UAVs) have become a subject of great interest in the field of flying systems, due to their maneuverability, agility and morphological capacities. They can be used for specific missions and in more congested spaces. Moreover, this novel class of UAVs is considered as a viable solution for providing flying robots with specific and versatile functionalities. In this paper, we propose (i) a new design of a transformable quadrotor with (ii) generic modeling and (iii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…7 that the SMC reduces the oscillation more than the PD. Especially at the time when a disturbance is applied to the system [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]s, not only the peak amplitude calculated with the SMC is smaller than that calculated with the PD, but the time required for the system to return to a minimum oscillation is also reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 that the SMC reduces the oscillation more than the PD. Especially at the time when a disturbance is applied to the system [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]s, not only the peak amplitude calculated with the SMC is smaller than that calculated with the PD, but the time required for the system to return to a minimum oscillation is also reduced.…”
Section: Resultsmentioning
confidence: 99%
“…These controllers are selected for this study because they are the most used for quadrotor control, as shown in Refs. [11,12,34,35,37]. The comparison between the SMC and the PD controllers has been made to assess the main contributions of this paper, that consists in the new dynamic configuration and vibration suppression over the quadrotor flight phases.…”
Section: Controllers Developmentmentioning
confidence: 99%
“…The FT control can be used to regain control of the quadrotor when partial loss of thrust generated by the propellers or complete propeller failure occurs. The authors in [9][10][11] proposed geometric changes in the structure of the quadrotor to compensate against any faulty behavior. The main impetus of this paper comes from the idea to introduce additional stability to help quadrotors in maintaining pose in 3D space and performing safe maneuverings despite losing one propeller or two opposing propellers.…”
Section: Introductionmentioning
confidence: 99%
“…They have many advantages compared to the fixed-wing drones in terms of maneuverability, structure and versatility. Moreover, they have a simple mechanical design, a small size and a low cost [1,2,3,4,5,6,7]. Quadrotors are widely exploited in military and civilian missions such as, search and rescue, mapping, protection of sensitive points, and infrastructure inspection [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%